Evaluation of the treatment patterns and economic burden of dysmenorrhea in Japanese women, using a claims database - Akiyama S; Tanaka E; Cristeau O; Onishi Y; Osuga Y (Dove Medical Press, 2017)
Sayako Akiyama,1 Erika Tanaka,2 Olivier Cristeau,3 Yoshie Onishi,4 Yutaka Osuga5 1Health Economics and Outcomes Research, 2Advocacy and External Affairs, Market Access, Bayer Yakuhin, Ltd., Tokyo, Japan; 3Health Economics and Outcome Research, Creativ-Ceutical, Paris, France; 4Creativ-Ceutical K.K., Tokyo, Japan; 5Obstetrics and Gynecology, Graduate School of Medicine, The University of Tokyo, Tokyo, Japan Purpose: This study aimed to describe treatment patterns and estimate health care resource utilization and associated costs among Japanese women with dysmenorrhea, using a claims database.Methods: This was a retrospective analysis using health insurance data from the Japan Medical Data Center, assessing female patients aged 18–49 years with newly diagnosed primary or secondary dysmenorrhea. Treatment pattern analyses focused on hormonal medications, analgesics, hemostatic agents, traditional Chinese medicine (TCM), and gynecological surgeries. Data were collected on health care resource utilization and costs associated with medications, imaging procedures, and inpatient and outpatient care in both patients and matched controls.Results: The analysis included 6,315 women with dysmenorrhea (3,441 primary; 2,874 secondary). The most commonly prescribed initial therapies were low-dose estrogen progestins (LEPs, 37.7%) and TCM (30.0%), with substantial differences between primary (LEPs: 27.4%, TCM: 38.8%) and secondary (LEPs: 50.2%, TCM: 19.5%) dysmenorrhea cohorts. Surgery was conducted in <5% of all patients. Both primary and secondary cohorts of dysmenorrhea had significantly higher mean total health care costs compared to controls within the 1-year period following diagnosis (Case-primary: 191,680 JPY [1,916 USD]; secondary: 246,488 JPY [2,465 USD], Control-primary: 83,615 JPY [836 USD]; secondary: 90,711 JPY [907 USD]) (p<0.0001). After adjusting for baseline characteristics, these costs were 2.2 and 2.9 times higher for primary and secondary dysmenorrhea cohorts, respectively, compared with matched controls, (both p<0.0001). The main driver of these excess costs was outpatient care, with eight additional physician visits per year among dysmenorrhea patients compared to controls (p<0.0001).Conclusion: Considerable heterogeneity in treatment patterns was observed, with relatively low utilization of LEPs in patients with primary dysmenorrhea and those treated by internal medicine physicians. Total annual health care costs were approximately 2–3 times higher in patients with dysmenorrhea compared to women without the condition. Keywords: dysmenorrhea, women’s health, treatment patterns, resource use and costs, economic burden, database analysis